Ovarian reserve - Maria Flavia Loho (Indonesian Journal of Obstetrics and Gynecology, 2010)
Objective: To asses ovarian reserve (OR) is important in infertility management that will undergo Assisted Reproductive Technology (ART) programs. using some methods, eg. physical measurements: ovarian volume, Antral follicle Count (AFC); Biomarker assay, indirect and direct methods, Day 3 FSH, Anti-Mullerian Hormone (AMH), Inhibin B. Method: Literature review in published studies which assessment the Ovarian Reserve. Conclusions: Assessment of ovarian reserve (OR) is very important to predict the outcome of ART programs. There were several methods to assessing the OR, but none as a single predictor. The best candidate for a single biomarker is AMH. [Indones J Obstet Gynecol 2010; 34-1:43-6] Keywords: predictor of ovarium reserve, assisted reproductive technology